Role of environmental factors in the spread of domestic trout in Mediterranean streams. (27th June 2013) - Splendiani, Andrea; Ruggeri, Paolo; Giovannotti, Massimo; Caputo Barucchi, Vincenzo
Summary: Overharvesting, habitat alteration and pollution have contributed to the decline of many wild populations of brown trout in Europe. Since the mid‐19th century, stocking with domestic strains has added a further threat to their genetic integrity. In this study, we adopted a landscape genetic approach to evaluate the role of environmental factors in promoting or hindering invasion by an alien genome. Two classes of molecular markers ( LDH‐C1* locus and mtDNA) were used to evaluate the level of introgression between native and domestic strains of brown trout in Central Italy. A multivariate method (redundancy analysis, RDA) was employed to find relationships between genetic diversity and 19 environmental variables that describe lithology, geomorphology, fish community and human activities. The RDA indicated that streams with more stable ecological conditions sustain almost pure native populations, whereas streams characterised by unpredictable hydrological conditions harbour populations with high levels of introgression or pure for foreign genotypes. Our study revealed that the outcome of supplementary stocking with hatchery‐reared brown trout is strongly linked to the environmental features of different drainage basins.